РАДИАЛЬНЫЙ ПРИРОСТ СОСНЫ ОБЫКНОВЕННОЙ В ОСТРОВНОМ МАССИВЕ БОРА ЛИШАЙНИКОВОГО ПЕЧОРСКОГО ЗАПОЛЯРЬЯ - Манов, А. (Федеральное государственное бюджетное учреждение науки Коми научный центр Уральского отделения Российской академии наук, 2014)
Рассматривается динамика радиального прироста сосны обыкновенной ( Pinus sylvestris L. ), произрастающей в условиях дефицита тепла и достатка влаги в переходной зоне лес-тундра. Выявлен высокий показатель автокорреляции первого порядка в индивидуальных хронологиях сосны. Построена обобщенная древесно-кольцевая хронология и установлен климатически обусловленный сигнал радиального прироста сосны на основные метеорологические показатели (температура воздуха, осадки). Dynamics of radial growth of Pinus sylvestris L. in conditions of heat deficiency and moisture sufficiency in transitive forest-tundra zone in the European northeast is considered. High enough coherence of individual rows of Pinus sylvestris L. radial growth allowed to make the generalized 217-year-long chronology. The analysis of tree-ring chronology has shown that many-year changeability of pineradial growth is caused by temperature fluctuations in summer months. Bymeans of response function a significant positive regression link (at P<0.05) of the generalized Pinus sylvestris L. chronology with temperature in June ( r=0,19) and July ( r=0,34) is identified. Intensity of climatic signal in the width of annual growth rings in time interval was unstable. The raised air temperature in the second quarter of XX century makes positive impact on pine growth from May till August ( r=0,12-0,42). The subsequent cold snap of climate occurring till the 1970-s, has led to decrease in reaction of radial growth to air temperature twice. The cold snap during this period promoted positive influence of temperature on pine radial growth from May till September. The large-scale warming of climate in northern latitudes begun in the end of XX century and proceeding till now does not cause any increase in reaction of pine radial growth on rise in temperature which has been observed in the 1920-1940-s of XX century. The decrease of positive influence of air temperature on pine radial growth from May till July ( r=0,003-0,37) in the Pechora Polar regions is identified.